2013
DOI: 10.1111/exd.12294
|View full text |Cite
|
Sign up to set email alerts
|

Activation of primary sensory neurons by the topical application of capsaicin on the epidermis of a re‐innervated organotypic human skin model

Abstract: Using an ex vivo skin-nerve preparation, skin and nerve cells were reconstituted into a single unit and maintained in a nutrient medium bath until required experimentally. Our objective was to use the epidermis as a relay for the induction of an electric current to the neurons following the topical application of capsaicin on the skin epidermis of the skin explant, an agonist of the TRPV1 channel implicated in pruritus and pain. After 10-20 days of coculture to form the re-innervated skin model, we applied a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
11
0
2
Order By: Relevance
“…The reinnervation of human skin explants with DRG neurons is a very satisfying model for sensitive skin [74,75]. In this model, it is possible to activate sensory neurons after the application of capsaicin on the epidermis, as showed by the modification of electric currents on patched nerve fibres and the release of neurotransmitters [76]. For the screening of putative active substances for sensitive skin, it is more convenient to use a co-culture of keratinocytes and neurons, which can be also activated by capsaicin or lactic acid [77].…”
Section: Consequences For In Vitro Models Of Sensitive Skinmentioning
confidence: 99%
“…The reinnervation of human skin explants with DRG neurons is a very satisfying model for sensitive skin [74,75]. In this model, it is possible to activate sensory neurons after the application of capsaicin on the epidermis, as showed by the modification of electric currents on patched nerve fibres and the release of neurotransmitters [76]. For the screening of putative active substances for sensitive skin, it is more convenient to use a co-culture of keratinocytes and neurons, which can be also activated by capsaicin or lactic acid [77].…”
Section: Consequences For In Vitro Models Of Sensitive Skinmentioning
confidence: 99%
“…On peut ainsi s'attendre à ce que, en fonction de l'agoniste choisi et de sa concentration, les proportions des neuropeptides libérés soient différentes. Il est possible de ré-innerver des explants de peau [12,32]. Toutefois, cette procédure, difficilement applicable à des biopsies provenant de patients, ne permet pas de moduler la composition cellulaire de l'explant et ne garantit pas l'élimination des cellules immunitaires cutanées et des fibres nerveuses du donneur (sectionnées lors de la biopsie), et dont les éléments qui subsistent après prélèvement sont susceptibles d'affecter la réponse du modèle.…”
Section: Les Modèles De Peau Innervésunclassified
“…Indeed, after discussions for many years, it has been clearly demonstrated that keratinocytes, which have been long been considered to be a simple physical support for FNEs, can play a sensory role, especially in noxious touch . Therefore, FNEs are not the exclusive transducers of painful information and keratinocytes must closely and specifically communicate with sensory neurons to convey sensory information, which ultimately leads to withdrawal behaviour.…”
Section: Premisesmentioning
confidence: 99%